Pendampingan Cara Perhitungan dan Pelaporan PPh 21 Karyawan RSIA Permata Hati Mataram - CA, BAMBANG (Jurnal Abdimas Independen, 2021)
This service aims to assist employees in calculating and reporting Income Tax (PPh) 21 on salaries and other receipts received by employees. The calculation of the amount of taxes uses excel while reporting uses the e-filling facility provided by the Director General of Taxes. The service method consists of 1) Lecture method, through this method participants are given knowledge and understanding through presentations by presenters and motivation to have the willingness to apply the application. This method is carried out for 1/2 hour, 2) The tutorial method Participants are given a guide on the steps for calculating PPh 21. This method is carried out for 1/2 hour., 3) A practice session, Participants practice the steps they have learned This method is carried out during 1 hour, 4) Discussion method Participants are given the opportunity to discuss the problems they face related to difficulties in calculation and reporting. This method is carried out for 1 hour. After the training, employees have been able to calculate PPh 21 and report via e-filling. The training challenge is that it is still necessary to improve the operation of excel applications and intermediate and advanced level formulas, while reporting requires repeated and continuous training.